Irrigated Soybean Leaf Photosynthesis in the Humid Subtropical Midsouth - H. Arnold Bruns (International Journal of Agronomy)
Photosynthesis (CER (μmol CO2mleaf area-2 s−1)), stomatal conductance (gsw), and intercellular [CO2] (Ci) of soybean (Glycine max L. Merr.) grown using the early soybean production system (ESPS) of the midsouth were determined. Three irrigated cultivars were grown using ESPS on Bosket (Mollic Hapludalfs) and Dundee (Typic Endoaqualf) soils in 2011 and 2012 at Stoneville, MS. Single leaf CER, gsw, and Ci were determined at growth stages R3, R4, and R5 using decreasing photosynthetic photon flux densities (PPFD, μmol m−2 s−1) beginning at 2000 PPFD and decreasing by 250 PPFD increments to 250 PPFD. Photosynthesis changes fit a quadratic polynomial for all fixed variables and range from ~6.0 and 9.0 CER at 250 PPFD and ~22.0 to 28.0 CER at 2000 PPFD. No cultivar differences in CER, gsw, or Ci were noted at any growth stage or site either year. In 2012, CER, gsw, and Ci were lower when measured at R5 than the two previous growth stages, which was not observed in 2011. The R5 sampling in 2012 had accumulated 39 to 70 more growing degree units at 10°C base temperature (GDU 10’s) than in 2011 and were likely more mature. Increased soybean yields from ESPS appear not to result from higher leaf CER.